How to become world champion and Olympic gold medalist in 50km race walking - Pupis, M.; Spisiak, M.; Toth, M. (Slovak Journal of Sport Science, 2017)
The aim of research was to compare the preparation of World champion and Olympic gold medalist in 50 km race walk for Olympic Games and WorldChampionship. As our research revealed, we recorded the biggest difference in volume of completed kilometres. In olympic year it was 4471 km, therefore it is about 1136 km less than during yearly training cycle (YTC) 2014/15 and the volume of completed kilometres was 3566 km and it presents about 1124 km less than YTC 2014/15. With intensity of walking 3:41-4:05 min.km-1 subject completed 56 km during Olympic year, 202 km less than it was in YTC 2014/15. With intensity of 4:06-4:20 min.km-1 he completed 165 km, equalled 114 km less than during YTC 2014/15. There were noticeable differences in special tempo and tempo's endurance as well. While in special tempo (4:21-4:40 min.km-1) subject completed 451 km, means about 247 km less than YTC 2014/15 and during intensity of 4:41-5:00 min.km-1 989 km, which is about 469 km less than YTC 2014/15. From a perspective of YTC, olympic year was worse in quantitative and also qualitative parameters. On the other hand last 8 weeks were very similar, which was crucial for result on Olympic Games.